2021
DOI: 10.3390/ijerph18189550
|View full text |Cite
|
Sign up to set email alerts
|

The Disappearance of Respiratory Viruses in Children during the COVID-19 Pandemic

Abstract: Background: Social distancing measures are used to reduce the spreading of COVID-19. The aim of this study was to assess the impact of local restrictions on the transmission of respiratory virus infections. Methods: we retrospectively analyzed the nasopharyngeal samples of all patients (0–18 years old) admitted with respiratory symptoms in a large Italian tertiary hospital during the last three seasons from 2018 to 2021. Results: A strong reduction in all viral respiratory infections was observed in the last s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
73
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 18 publications
7
73
1
Order By: Relevance
“…Nevertheless, the apparently low incidence of SARS-CoV-2 infections in the pediatric populations has been confirmed in several studies in hospitalized patients. 9 , 17 Furthermore, all of our patients were seen in an outpatient setting reflecting the general pediatric population and infection activity more accurately than hospitalized patients do.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the apparently low incidence of SARS-CoV-2 infections in the pediatric populations has been confirmed in several studies in hospitalized patients. 9 , 17 Furthermore, all of our patients were seen in an outpatient setting reflecting the general pediatric population and infection activity more accurately than hospitalized patients do.…”
Section: Discussionmentioning
confidence: 99%
“…resulted in a drastic reduction in incidence of respiratory viruses including influenza, adenovirus, and RSV. On the contrary, RV stood out and appeared to cocirculate with SARS-CoV-2 at a similar rate to its habitual seasonal patterns, despite the reduction in contacts due to the public health measures [61,62]. A higher infectivity and prevalence in children, who are less subject to social distancing measures and mask wearing, may explain the lesser impact of public health measures on reducing RV transmissions in comparison to other respiratory viruses [63].…”
Section: Rhinovirus Seasonalitymentioning
confidence: 95%
“…At the beginning of the emergency, public health measures revealed that the control of SARS-CoV-2 modified the epidemiology of other respiratory viruses including RSV. Consequently, in Italy, as well as in other countries, a strong reduction in all viral respiratory infections was observed in the last season (2020–2021), compared with the previous seasons [ 5 , 6 , 7 ].…”
mentioning
confidence: 97%
“…Evidence suggests that children who experienced RSV infection early in life are at risk of developing wheezing, hyperactive airways, bronchospasm, and asthma later in life. Overall, these factors contribute to substantial health care use and economic burden of RSV disease long-term complications, caregiver stress, and loss of work productivity [ 4 , 5 ]. To date, no effective and specific treatment is available to cure RSV, as therapeutic measures are still undergoing preliminary research.…”
mentioning
confidence: 99%